Influence of elektromagnetics vibrations refraction index to pseudodistance accuracy in GPS measurements - Jonas Skeivalas (Geodesy and Cartography, 2012)
Research demonstrates the accuracy of pseudo distance measurements evaluating the impact of the refraction index and spread speed of vibrations in the vacuum. It also shows the influence of the refraction index of vibrations and spread speed errors to the errors of pseudo distances. Establishing the refraction index of vibrations has the major impact on the accuracy of pseudo distances performing GPS measurements. The limited possibilities of evaluating the measurements of atmosphere parameters and marked fluctuations in values define the estimation errors of the refraction index of vibrations. The influence of establishing errors in vibration speed in the vacuum on errors occurring in pseudo distances is expressed at a much lower row (level). The article presents the equations for evaluating the refraction index of vibrations and the measured accuracy of pseudo distances depending on the known accuracy of the values of atmospheric parameters.